BAYANGAN GELAP DI DUNIA AKADEMIK: PENGARUH SOSIAL BUDAYA DALAM MENYIKAPI FENOMENA BULLYING MELALUI SOSIALISASI EDUKATIF DI SMAN 5 TANJUNGPINANG - Suherry, Suherry; Junriana, Junriana; Fadilla, Safrika Nur; Riyadi, Ridho Aufa; Safrika Nur Fadilla, Safrika Nur Fadilla (Jurnal Pepadu, 2025)
The phenomenon of bullying in the school environment is still often considered as part of the dynamics of social interaction, even though its impact on students' mental health is very significant. The community service activity carried out at SMAN 5 Tanjungpinang City aims to increase awareness of grade 10 students about the negative impacts of bullying, both in physical and non-physical forms, as well as the socio-cultural influences in strengthening this behavior. The main focus of this service is to provide an understanding of the forms of bullying that are often not recognized as violations, as well as the importance of building an inclusive and safe school culture. The methods used are socialization through material presentation, group discussions, and simulations on how to support victims of bullying. The results of this service show an increase in student awareness of the dangers of bullying, as well as changes in their attitudes towards the importance of respecting differences and creating a safer environment. However, the biggest challenge is changing the culture that has been formed, which requires the active role of teachers, students, parents, and the community in creating long-term change.